Social determinants of pertussis and influenza vaccine uptake in pregnancy: a national cohort study in England using electronic health records. Issue 6 (21st June 2021) - Walker, Jemma L; Rentsch, Christopher T; McDonald, Helen I; Bak, JeongEun; Minassian, Caroline; Amirthalingam, Gayatri; Edelstein, Michael; Thomas, Sara
Abstract : Objective: To examine the social determinants of influenza and pertussis vaccine uptake among pregnant women in England. Design: Nationwide population-based cohort study. Setting: The study used anonymised primary care data from the Clinical Practice Research Datalink and linked Hospital Episode Statistics secondary care data. Participants: Pregnant women eligible for pertussis (2012–2015, n=68 090) or influenza (2010/2011–2015/2016, n=152 132) vaccination in England. Main outcome measures: Influenza and pertussis vaccine uptake. Results: Vaccine uptake was 67.3% for pertussis and 39.1% for influenza. Uptake of both vaccines varied by region, with the lowest uptakes in London and the North East. Lower vaccine uptake was associated with greater deprivation: almost 10% lower in the most deprived quintiles compared with the least deprived for influenza (34.5% vs 44.0%), and almost 20% lower for pertussis (57.7% vs 76.0%). Lower uptake for both vaccines was also associated with non-white ethnicity (lowest among women of black ethnicity), maternal age under 20 years and a greater number of children in the household. The associations between all social factors and vaccine uptake were broadly unchanged in fully adjusted models, suggesting the social determinants of uptake were largely independent of one another. Among 3111 women vaccinated against pertussis in their first eligible pregnancy and pregnant again, 1234 (40%) were not vaccinated in their second eligible pregnancy. Conclusions: Targeting promotional campaigns to pregnant women who are younger, of non-white ethnicity, with more children, living in areas of greater deprivation or the London or North East regions, has potential to reduce vaccine-preventable disease among infants and pregnant women, and to reduce health inequalities. Vaccination promotion needs to be sustained across successive pregnancies. Further research is needed into whether the effectiveness of vaccine promotion strategies may vary according to social factors.